Prevalence and factors associated with knowledge and access to delivery services at primary health care facilities amongst indigenous women in Khagrachhari district Bangladesh – A cross-sectional study. (November 2020) - Akter, Shahinoor; Rich, Jane L.; Davies, Kate; Inder, Kerry J.
Abstract: Objective: To estimate the prevalence of facility delivery knowledge and access during childbirth amongst Indigenous women in the Chittagong Hill Tracts, Bangladesh and to identify factors associated with facility delivery service utilisation. Design: A cross-sectional study design using a structured self-report survey. Setting: Two Upazilas (subdistricts) of Kharachhari hill district of the Chittagong Hill Tracts. Participants: Indigenous women of reproductive age (15–49 years) within 36 months of delivery. Measurements and findings: A modified national survey about accessing maternal health services, including delivery services was administered to all Indigenous women that met eligibility, guided by community leaders. Data collected included socio-demographic characteristics and reproductive history. Main outcome variables were the proportion of women having prior knowledge about and access to facility delivery services for childbirth in the three years prior to the survey. Secondary outcomes were sources of information about facility delivery services, decision making about delivery place, and factors associated with knowledge and attendance at facility delivery services. Factors associated with knowledge and attendance were estimated using logistic regression with results reported as adjusted odds ratios and 95% confidence intervals. With an 89% response rate, a total of 438 Indigenous women (220 Chakma, 100 Marma, 118 Tripura) participated in the survey, and 75% were aged 16–29 years. Relatives played a vital role as a source of information about delivery services (59%). Nearly three-quarters (73%) were aware of facility delivery services, however, prevalence of accessing delivery services was 33% ( n  = 143; 95% CI 0.28–0.37). Relatives were the key decision-makers for accessing facility delivery services (60%). Independent factors associated with knowledge about facility delivery were higher household income (AOR 5.3, 95%CI 2.2–13); having knowledge of nearest health care facilities (AOR 5.8, 95%CI 3.0–11); and attending antenatal care visits during last pregnancy (four or more AOR 3.1, 95% CI 1.3–7.2 and one to three visits AOR 2.7, 95% CI 1.5–5.0). Independent factors associated with accessing facility delivery services at childbirth were attending antenatal care visit; having access to media; higher level of education of partners; and residing at Khagrachhari Sadar compared to Matiranga subdistrict. Key conclusions and implications for practice: Indigenous women in Chittagong Hill Tracts, Bangladesh have sub-optimal knowledge of, and attendance at, facility delivery services for childbirth. Maternal health related interventions should target Indigenous women in order to educate and motivate them to access facility delivery services at childbirth. Rigorous research is needed to explore Indigenous cultural practices related to childbirth that might influence their access to facility delivery services.